2013
DOI: 10.1136/heartjnl-2013-304225
|View full text |Cite
|
Sign up to set email alerts
|

The unnatural history of an atrial septal defect: Longitudinal 35 year follow up after surgical closure at young age

Abstract: Very long-term outcome after surgical ASD closure in childhood shows good survival and low morbidity. Early surgical closure prevents pulmonary hypertension and reduces the occurrence of supraventricular arrhythmias. Early postoperative arrhythmias are predictive for the need for pacemaker implantation during early follow-up, but the rate of late pacemaker implantation remains low. Although RVEF was unexpectedly found to be decreased in one-third of patients, the functional status remains excellent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 29 publications
1
53
0
Order By: Relevance
“…Noninvasive tests have an approximately 90% positive predictive value and 30% negative predictive value for identifying pathways with lifethreatening properties. 294,295,297 If noninvasive evaluation suggests that the accessory pathway conducts poorly in the anterograde direction, although risk of life-threatening events is likely lower, the EP study still may be useful because of patient symptoms.…”
Section: Cavotricuspid Isthmus-dependent Atrial Fluttermentioning
confidence: 99%
See 1 more Smart Citation
“…Noninvasive tests have an approximately 90% positive predictive value and 30% negative predictive value for identifying pathways with lifethreatening properties. 294,295,297 If noninvasive evaluation suggests that the accessory pathway conducts poorly in the anterograde direction, although risk of life-threatening events is likely lower, the EP study still may be useful because of patient symptoms.…”
Section: Cavotricuspid Isthmus-dependent Atrial Fluttermentioning
confidence: 99%
“…The noninvasive findings that identify a pathway not capable of maintaining rapid conduction during AF include intermittent loss of conduction over the accessory pathway on the resting ECG or during ambulatory monitoring, or abrupt loss of pre-excitation during exercise testing (Figure 16). [294][295][296][297] The ECG should be evaluated closely to make certain the delta wave is truly absent, as accessory pathways, especially left lateral pathways, may demonstrate varying degrees of pre-excitation because of fusion between conduction over the accessory pathway and through the AV node. This may give the appearance of loss of pre-excitation if the subtle delta wave is not identified.…”
Section: IIImentioning
confidence: 99%
“…In our patient group, other reasons for lack of cerebrovascular embolic events may include entry through the pulmonary veins only for the left heart catheterization, and not dealing with high-risk vessels for plaque embolization such as the aorta. Furthermore, complete closure of the defect with no residual shunt following the procedure and young age may be additional factors contributing to the lack of any cerebrovascular complications (21). The total duration of catheterization and fluoroscopy are independent risk factors for the occurrence of microembolic infarctions, since the increased duration allows the catheter to interact with vessel wall during the manipulation and form thrombus (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…3,9 Nevertheless, studies suggest residual impaired exercise capacity after closure in a substantial fraction of patients. [3][4][5] Recently, Cuypers et al 3 reported impaired exercise capacity, increased RV volumes, and mild RV dysfunction in one-third of repaired-ASD patients, using echocardiography and cardiac magnetic resonance imaging. Using similar methodology, de Koning et al 10 documented residual RV dilatation but normal exercise capacity.…”
Section: Ventricular-arterial Interactionmentioning
confidence: 99%
“…However, while most patients have resolution of RV dilation, some studies demonstrate that, in a sizable subset of patients, RV dilation may persist and maximal exercise capacity may remain impaired in longterm follow-up. [3][4][5] In theory, exercise impairment due to cardiovascular limitation could result from persistent, underrecognized changes in the RV and the pulmonary arterial (PA) bed. Epstein and colleagues 6 published unique invasive exercise-hemodynamics data for asymptomatic patients who had undergone ASD closure.…”
Section: Introductionmentioning
confidence: 99%